855 Cutaneous adverse events of immune checkpoint inhibitor therapy: incidence and types of reactive dermatoses. (9th November 2020) - Le, Thomas; Kaul, Subuhi; Wongvibulsin, Shannon; Cappelli, Laura; Naidoo, Jarushka; Semenov, Yevgeniy; Kwatra, Shawn
Abstract : Background: Cutaneous toxicities are a common and potentially serious complication of programmed cell death receptor PD-1 immune checkpoint inhibitor (anti-PD-1 ICI) therapy. These cutaneous immune-related adverse events (irAEs) have been reported in up to one-third of treated patients, and are usually the first adverse event to occur with immune checkpoint inhibitor use. Due to non-specific reporting in many anti-PD-1 clinical trials, little data is available on the real-world incidence and morphology of cutaneous irAEs. Understanding the spectrum of cutaneous adverse events in real-world clinical environments is necessary to support clinical awareness, diagnosis, and management when undergoing anti-PD-1 therapy. We aimed to describe the incidence of a known spectrum of skin dermatoses in the setting of ICI, and also identify the risk of these adverse events compared with the general population. Methods: This was a cross-sectional study of anti-PD-1 (pembrolizumab or nivolumab) treated patients at a tertiary healthcare institution from September 2014 to November 2018. Inflammatory dermatoses occurring in the setting of anti-PD-1 therapy (pembrolizumab or nivolumab) was compiled using our institutional experience with ICIs and case studies and reports on PUBMED. Selected dermatologic events following immunotherapy were identified in the electronic medical record. Unadjusted odds ratios (OR) for the development of a given cutaneous event was calculated by comparison to the non-ICI general population. Results: Of the 1, 857 patients treated with anti-PD-1 ICIs, there were 1, 079 patients treated with nivolumab, 821 patients treated with pembrolizumab, and 43 patients treated with both pembrolizumab and nivolumab. There were 254/1857 (13.7%) patients that developed one of the 28 different dermatoses identified from literature review following anti-PD-1 ICIs. Compared with the general population, patients treated with anti-PD-1 had a greater risk for development of mucositis (OR 65.7, 95% CI 35.0-123.3), xerostomia (OR 11.9, 95% CI 8.4-16.8), pruritus (11.3, 95% CI 8.9-14.3), and lichen planus/lichenoid dermatitis (OR 10.7, 95% CI 5.6-20.7) compared to the control group. Conclusions: We report the frequency of dermatoses encountered in the setting of ICI therapy, both commonly (pruritus, rash, vitiligo) and more rarely reported (scleroderma, urticaria). As nivolumab and pembrolizumab currently make the bulk of approvals for ICI therapy, this analysis of real-world irAE incidence will be of use to treatment teams to improve quality of life and ensure ICI therapy adherence. Furthermore, this analysis sets the stage for future in-depth investigation of these cutaneous toxicities, including dose-response relationships, prognostic information from cutaneous events, and optimal treatment strategies. Ethics Approval: This study did not require IRB approval, due to the use of anonymized and de-identified aggregate-level data.